An Interprofessional Substance Use Disorder Course to Improve Students' Educational Outcomes and Patients' Treatment Decisions. (25th June 2019) - Muzyk, Andrew; Mullan, Patricia; Andolsek, Kathryn M.; Derouin, Anne; Smothers, Zachary; Sanders, Charles; Holmer, Shelley
Abstract : Purpose: Substance use is a public health concern. Health professions organizations recommend improvements in substance use disorder (SUD) education. Mezirow's Transformative Learning Theory was used as the educational framework to develop a course that would provide students with opportunities to improve their understanding of SUDs; to assess, challenge, and reflect on their attitudes toward patients with SUDs; to receive direct observation, assessment, and feedback on behavior change counseling; and to engage in interprofessional education. The study's purpose was to evaluate the impact of an interprofessional SUD course on students' educational outcomes and their attitudes toward interprofessionalism. Method: Students from several health professions—medicine, pharmacy, physician assistant, nursing, and social work—attended a monthly interprofessional education SUD course starting in spring 2018. The course, taught by an interprofessional faculty, consisted of four interactive classes focused on empathy and recognizing personal bias; behavioral change counseling; and recognition, screening, and treatment of SUDs. Students attended a 12-step recovery meeting and had an optional opportunity to counsel a patient using behavioral change counseling. Results: Seventy-eight students completed the course. Students demonstrated significant improvements in their attitudes toward patients with SUDs and toward interprofessionalism, as measured by the Substance Abuse Attitudinal Scale and the Student Perceptions of Interprofessional Clinical Education survey. Nearly 70% of students counseled a patient with an SUD and 93% of counseled patients agreed to follow-up care. Conclusions: The course (1) enriched students' understanding, attitudes, and behaviors toward patients with SUDs and toward interprofessional collaboration and (2) positively influenced patients' treatment decisions.